Peningkatan Hasil Belajar IPA melalui Metode Demonstrasi pada Siswa Kelas III SDI Tetandara, Kabupaten Ende - Arnesta Patrisia Wende; Yuliani Sepe Wangge; Finsensius Mbabho (Program Studi PGSD Universitas Flores, 2020)
This research aims: (1) to know how to implement natural science learning with demonstration method in grade III children in SDI Tetandara, Ende District. (2) To find out the improvement of natural sciences through demonstration methods in grade III students at SDI Tetandara, Ende District. The type of research used is class action research (CAR) and the subject in the study was a grade III student in SDI Tetandara which amounted to 20 people. Data collection techniques using observation techniques, tests, documentation and interviews. Data is analyzed descriptively by calculating the average and percentage of the submission in each cycle. Based on the results of data analysis and discussion of the results shows that the use of demonstration methods has an influence on the outcome of learning natural sciences, on material objects. This is evident from the teacher's ability to manage student learning outcomes in the learning process. Visible from the Pretest result with an average value obtained value of 48. Then, the student's value increased from the cycle I study results showed the average grade III value was 57 and was in the category enough and the percentage was 35%. In Cycle II Learning, the results gained increased by the percentage of the compensation reached 100% with the average value gained 84.5. This value indicates an increase in the results gained on cycle learning I. These results show that demonstration methods can improve the results of natural Science study on students in class III in SDI Tetandara District of Ende.